Why we write (nuclear) history. Issue 3 (19th September 2017) - Hecht, David K.
Abstract : Nuclear history always compels. Scholars (and readers) can immerse themselves in the existential threat posed by the atomic bomb and its successor weapons, the tantalizing prospect of carbon-free energy, or the study of a natural phenomenon deeply at odds with our everyday experience of the world. There is thus always something profound at stake when we write nuclear history – be it physical, economic or intellectual. And while it may seem that the end of the Cold War should have diminished the academic attention accorded to the subject, it actually just allowed the historiography to evolve. To the wealth of technical and political studies that once dominated nuclear history, we can now add a host of excellent cultural, environmental, literary and transnational studies. Those of us who entered the field shortly after the break-up of the Soviet Union have been able to follow these developments first-hand, from the initial uncertainty of where nuclear history would go without its original raison d'être to seeing the possibilities opened up in a post-Cold War world. The books under review here provide important and timely additions to this historiography. Luis A. Campos's Radium and the Secret Life provides a rigorous and compelling account of the uses of radium in early twentieth-century biology; Timothy J. Jorgensen's Strange Glow: The Story of Radiation offers an accessible and illuminating analysis of the benefits and risks of radiation. The books also make for a fascinating juxtaposition. They complement each other well, but also contain some intriguing differences that allow us to reflect on the nature of nuclear history in the early twenty-first century.